Serum levels of iCAF‐derived osteoglycin predict favorable outcome in pancreatic cancer. Issue 3 (19th September 2022) - Dings, Mark P. G.; Manoukian, Paul; Waasdorp, Cynthia; Quik, Judith S. E.; Strijker, Marin; Lodestijn, Sophie C.; van Neerven, Sanne M.; Moreno, Leandro F.; de Oliveira, Rodrigo Leite; Bonsing, Bert A.; Bruno, Marco J.; Busch, Olivier R.; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by abundant stroma, the main cellular constituents of which are cancer‐associated fibroblasts (CAFs). Stroma‐targeting agents have been proposed to improve the poor outcome of current treatments. However, clinical trials using these agents showed disappointing results. Heterogeneity in the PDAC CAF population was recently delineated demonstrating that both tumor‐promoting and tumor‐suppressive activities co‐exist in the stroma. Here, we aimed to identify biomarkers for the CAF population that contribute to a favorable outcome. RNA‐sequencing reads from patient‐derived xenografts (PDXs) were mapped to the human and mouse genome to allocate the expression of genes to the tumor or stroma. Survival meta‐analysis for stromal genes was performed and applied to human protein atlas data to identify circulating biomarkers. The candidate protein was perturbed in co‐cultures and assessed in existing and novel single‐cell gene expression analysis from control, pancreatitis, pancreatitis‐recovered and PDAC mouse models. Serum levels of the candidate biomarker were measured in two independent cohorts totaling 148 PDAC patients and related them to overall survival. Osteoglycin (OGN) was identified as a candidate serum prognostic marker. Single‐cell analysis indicated that Ogn is derived from a subgroup of inflammatory CAFs. Ogn ‐expressing fibroblasts are distinct from resident healthy pancreatic stellate cells and arise during pancreatitis. Serum OGN levels were prognostic for favorable overall survival in two independent PDAC cohorts (HR = 0.47, P  = .042 and HR = 0.53, P  = .006). Altogether, we conclude that high circulating OGN levels inform on a previously unrecognized subgroup of CAFs and predict favorable outcomes in resectable PDAC. Abstract : What's new? The heterogeneity of cancer‐associated fibroblasts (CAFs) in pancreatic ductal adenocarcinoma (PDAC) with both tumor‐promoting and tumor‐suppressive properties has recently been recognized. Our study identifies osteoglycin as a distinct marker for an inflammatory and tumor‐suppressive CAF subpopulation. The favorable prognostic significance of high serum osteoglycin levels was observed in a cohort of 40 patients with resected PDAC and further validated in a nationwide multicenter cohort of 108 patients. The findings point to osteoglycin as a potential noninvasive biomarker that not only predicts favorable clinical outcomes but also distinguishes a novel CAFs subtype.